Allogeneic hematopoietic stem cell transplantation to cure sickle cell disease: A review - Bhalla, Nishka; Bhargav, Anjali; Yadav, Sandeep Kumar; Singh, Aloukick Kumar (Frontiers in Medicine, 2023)
Sickle cell disease (SCD) had first been mentioned in the literature a century ago. Advancement in the molecular basis of the pathophysiology of the disease opens the door for various therapeutic options. Though life-extending treatments are available for treating patients with SCD, allogeneic hematopoietic stem cell transplantation (HSCT) is the only option as of yet. A major obstacle before HSCT to cure patients with SCD is the availability of donors. Matched sibling donors are available only for a small percentage of patients. To expand the donor pool, different contrasting approaches of allogeneic HSCT like T-cell replete and deplete have been tested. None of those tested approaches have been without the risk of GvHD and graft rejection. Other limitations such as transplantation-related infections and organ dysfunction caused by the harsh conditioning regimen need to be addressed on a priority basis. In this review, we will discuss available allogeneic HSCT approaches to cure SCD, as well as recent advancements to make the approach safer. The center of interest is using megadose T-cell-depleted bone marrow in conjugation with donor-derived CD8 veto T cells to achieve engraftment and tolerance across MHC barriers, under reduced intensity conditioning (RIC). This approach is in phase I/II clinical trial at the MD Anderson Cancer Centre and is open to patients with hemoglobinopathies.